Reimagining the grain silo of Ronehamn; Adaptive reuse of rural industrial heritage - Escabarte Svärd, Daniel; Brose, Linnea (My University, 2026)
In Sweden, numerous mid-20th-century concrete grain silos stand vacant. They represent both opportunities and challenges for the existing industrial heritage and our built typology. This thesis investigates a transformation of the grain silo in Ronehamn, a small village on Gotland, and researches the potential of adaptive reuse to prolong its lifetime. Through a combination of literature studies, case analyses, site visits, and stakeholder interviews, a pragmatic design proposal grounded in practical realities is presented. It aims to align with local needs and is motivated by and analysed through technical and sustainable building practices. The theoretical framework relies on the theory of adaptive reuse and the 9Rs model of reuse, combined with design concepts of aemulatio and genius loci. The core of this thesis is to demonstrate that transformation projects are crucial to ensure a sustainable development of the built typology. This practice reduces environmental impact by reusing existing structures, preserves embodied carbon, and minimises construction waste. Instead of demolishing and rebuilding, transformation extends the life of built resources and supports circular design principles. Apart from the ecological benefits, this practice helps to maintain cultural identity and revitalises communities by giving new purpose and value to obsolete buildings. The presented design proposal demonstrates how such a transformation can be carried out, both concerning the technical building aspects and how the existing building structure, transformed into new functions, can create added value in the local context. This thesis contributes to the discourse on industrial heritage reuse, offering strategies to extend building lifespans, preserve cultural identity, and reduce environmental impact through an architectural proposal that makes an abandoned structure accessible.
Keywords: transformation concrete structure aemulatio coastal proximity